Community economic recovery through the collaboration with tourist rickshaws in the old city of semarang - Arjuna Putra Sifa; Aditya Gema Fajariandi; Joseph Aldo Irawan; Emik Rahayu (Journal of Gastro Tourism, 2023)
Pedicab is a three-wheeled mode of transportation in ancient times where ancient people used pedicabs as a means of transportation to their destination. The tourist pedicabs in the Old City of Semarang have had a major impact on the economic recovery of the city of Semarang, and the tourist pedicabs are a form of local culture for the people of Semarang. It is indeed not easy for the Municipal Government of Semarang to implement a pedicab tour plan in the Old City of Semarang, because before organizing pedicab tours, the government must talk to small and medium business actors, especially pedicab tour owners. The method used in this assignment is a qualitative descriptive method using grounded theory of real conditions.